(3GdfXe GdEbJUGOjI GdeYGUQI (B/s - (3GdYhVj, QaYJ GdSjOs ((3GdEScfOQjI(B: s (3OGQ GdJYdje GdLGeYj(B, s, 2020)
(3JfGhd gPG GdcJGH ehVhY GdfXe GdGbJUGOjI GdeYGUQI MjK JWQb Gdi GdYhdeI hGdQCSeGdjI HCbdGe eacQjf ZQHjjf (B( (3aQGfSjS ahchjGeG h Uehjd gjfJfLJhf , h gGfS HjJQ eGQJjf , gGQdOTheGf(B) (3, hGdeOGQS GdGbJUGOjI GdGTJQGcjI(B. s
(3HHdjhZQGajG U(B.169s
Keywords: (3GdETJQGcjIs; (3GdQCSeGdjIs; (3GdfXe GdEbJUGOjIs